Descriptor-based morphometric diversity and palynological studies in Jasmine (Jasminum spp.) - MADHAVI, KURABALAKOTA; AWATI, MALLIKARJUN G; SHIROL, A M; P, PAVAN KUMAR; KUMAR, DEVARAI LAVA; JAIN, RITU; HIREMATH, VARUN M; A, POOJA (The Indian Journal of Agricultural Sciences, 2025)
The study was carried out during 2019–20 at the College of Horticulture, University of Horticultural Sciences, Bagalkote, Karnataka to characterize morphometric traits and pollen biology of jasmine (Jasminum spp.) using DUS descriptors and multivariate analysis across 12 genotypes. The experiment was laid out in a randomized complete block design (RCBD) with three replications. The highest coefficient of variation for quantitative traits ranged from 11.57% (plant spread)–99.31% (flowers/inflorescence). Variability in qualitative traits ranged from dimorphic (growth type and habit) to polymorphic (flower colour). Significant positive correlations were observed between floral traits and yield attributes. Pollen viability was highest in Jasminum auriculatum (Bagalkote local) at 75.72%, followed by Jasminum grandiflorum cv. CO1 Pitchi at 69.39%, and Jasminum nitidum (TNAU) at 65.42%. Principal component analysis showed PC1 and PC2 accounted for 28.40% (leaf blade dimensions, bud diameter, petal count) and 23.73% (bud length, corolla tube length, inflorescences/plant) of total variation. These findings aid in selecting parent plants for jasmine improvement and protecting new varieties under the PPVFR Act, 2001.